U11 snRNA interacts in vivo with the 5' splice site of U12-dependent (AU-AC) pre-mRNA introns. - Kolossova, I (1997)
A notable feature of the newly described U12 snRNA-dependent class of eukaryotic nuclear pre-mRNA introns is the highly conserved 8-nt 5' splice site sequence. This sequence is virtually invariant in all known members of this class from plants to mammals. Based on sequence complementarity between this sequence and the 5' end of the U11 snRNA, we proposed that U11 snRNP may play a role in identifying and/or activating the 5' splice site for splicing. Here we show that mutations of the conserved 5' splice site sequence of a U12-dependent intron severely reduce correct splicing in vivo and that compensatory mutations in U11 snRNA can suppress the effects of the 5' splice site mutations to varying extents. This provides evidence for a required interaction between U11 snRNA and the 5' splice site sequence involving Watson-Crick base pairing. This data, in addition to a report that U11 snRNP is bound transiently to the U12-dependent spliceosome, suggests that U11 snRNP is the analogue of U1 snRNP in splicing this rare class of introns.